Santa Fe dead - Woods, Stuart (New York : G.P. Putnam's Sons, 2008)
Ed Eagle finds the tables turned when he testifies as a witness for the prosecution in the trial of his ex-wife, who has been a very, very bad girl.
Keywords: Attorney and client -- Fiction; Eagle, Ed (Fictitious character) -- Fiction; Legal stories; Mystery fiction